Processos avaliativos em classes de pré-escola da Rede Municipal de Cuiabá : uma análise dos relatórios individuais de avaliação dos alunos - Pereira, Ana Elias Cardoso (2004)
Trough this searching, we tried to analise the evaluating reports of individual nursery groups from municipal teaching net of Cuiabá city, in Mato Grosso, Brazil. In order of knowing what teachers have registered about their students, identifying qhich aspects of the education process are privileged in these registers. Based in this analysis it’s important to understand the conceptions of the evaluation that are shown in those registers. The metodological approach that was made use of wsa the interpretive value, prevailing the descritive character of data. The doccumental analysis had beem evident even more appropriated to the development of the searching, considering the students individual reports from nursery groups. They were made during the year 2002 and are our main data source. In spite of the techinique is still not much explored in the education section, and in other areas for social action, established by Lüdke & Andre (1986): “a valuable approaching techniques of quantity data, supplying the information which were taken by other ones are caring new aspects of a them or a problem”. A number of 316 problems were anlysed and some of them can be resumed in therms of contents. The registers that were analysed show the enormous amount of turning to cognitival, social behavioral, psycomotor and postural aspects. Moreover revealing a smaller number of turnings related to the development of the autonomy or to the symbolical representation, besides the almost total absence of identity questions. As regards the way of writing, the registers show a quite distancing characteristics of the construtivism evaluation which reveal a distnce from the aspects that were mentioned before, that are essencials to this point of view, as a function of an interactive and reflexive character. From this conception point, the evaluation process is expressed by the registers. The results are perfect if anlysed through four teachers reports, who had taken part of this search, and they make a suggestion of getting a better expression of the elements related to the tradicional conception of evaluation. However, there are also the sgnis of construtivist elements, mainly showed by the appearance of individual character and the enphasys of the reasoning. Both analysis realized, the first about the contents and the way of registering, and the second about the conceptions, are expressed at the reports that emerging results tumed to the traditional perspetives, apart of cconstuctivst rehearsals.